Comparison of chemical characterization and oxidative stability of Lycium barbarum seed oils: A comprehensive study based on processing methods. Issue 9 (19th August 2022) - Zhang, Yu; Li, Xiaolong; Xu, Yuanyuan; Wang, Mengze; Wang, Fengjun
Abstract : Abstract: Five different processing methods (cold pressing, hot pressing, solvent extraction, ultrasound‐assisted solvent extraction, and supercritical fluid extraction) were evaluated to extract oils from Lycium barbarum ( L. barbarum ) seeds based on the lipid composition, minor bioactive components, and oxidative stability of oils. A large proportion of unsaturated fatty acids was detected in the L. barbarum seed oil, especially linoleic acid (65.24–66.26%). Minor bioactive components were abundant in L. barbarum seed oils, including tocopherols (292.65–488.49 mg/kg), phytosterols (9606.31–166, 684.77 mg/kg), polyphenols (35.65–113.87 mg/kg), and carotenoid (4.17–46.16 mg/100 g). Specifically, the phytosterol content was higher than that of other common oils. Comparing the different processing techniques, ultrasound‐assisted solvent extraction provided the highest extraction yield and recovery. The quantities of tocopherols, phenols, and phytosterols in hot‐pressed oil were higher than those in oils extracted from other methods, and thus it had the best oxidative stability. L. barbarum seed oils extracted by different techniques showed various characteristics and could be distinguished through principal component analysis and hierarchical cluster analysis. Practical Application: L. barbarum seed oil is a potentially underutilized oil resource with abundant essential fatty acid and phytosterol, which owns great value to apply in the nutritional, cosmetic, and medicinal fields. Hot pressing is an efficient method to produce L. barbarum seed oil for health care with high nutritional value and good quality, which can also be easily implemented on an industrial scale.